Biomedical materials (Springer, 2009)
Biomedical Materials provides a comprehensive discussion of contemporary biomaterials research and development. Highlighting important topics associated with Engineering, Medicine and Surgery, this volume reaches a wide scope of professionals, researchers and graduate students involved with biomaterials. A pedagogical writing style and structure provides readers with an understanding of the fundamental concepts necessary to pursue research and industrial work on biomaterials, including characteristics of biomaterials, biological processes, biocompatibility, and applications of biomaterials in implants and medical instruments.